Could it be gluten? Additional skin conditions associated with celiac disease. (2nd July 2021) - Klemm, Natasha; Gooderham, Melinda J.; Papp, Kim
Abstract: Celiac disease is a multifactorial, inflammatory disorder initiated and sustained by the ingestion of gluten. Occurring across a broad population, the intestinal and extraintestinal manifestations of celiac disease are variable in severity and may be nonspecific in presentation. Given that environmental, genetic, and immune factors involved in the pathogenesis of celiac disease that the digestive tract and skin share many characteristics, and with a prevalence of 0.5–1% in most populations, it is reasonable to consider varying presentations of skin conditions that are linked with celiac disease. The association between celiac disease and skin conditions has been discussed earlier, but new studies have emerged suggesting cutaneous involvement in addition to dermatitis herpetiformis. We review the current literature identifying the relationship and potential mechanisms between celiac disease and various skin conditions.